Turkey 2007 - Turkey 2007 (Directorat General of Press and Information of the Prime Ministry, 2007)
"Turkey 2007" is a reference book that can always be benefited from concerning the legal order, political and democratic structure of Modern Turkey and the reforms in this area; political, economic, social, cultural and historical characteristics and also information about fundamentals in foreign policy. This study is updated every year and supported with original photos is published in Turkish, English, German, French, Arabic, Russian, Spanish and Japanese.